2004
DOI: 10.1111/j.1525-1594.2004.07383.x
|View full text |Cite
|
Sign up to set email alerts
|

Component Engineering for an Implantable System

Abstract: Component engineering is important for the development of implantable-type rotary blood pumps (RP). The authors are conducting elementary development of an implantable artificial heart. A sensor system detects information in the living body. An automatic control system performs the drive control. Energy is provided by a transcutaneous energy transmission system (TETS). Various artificial hearts are being created. Miniaturization resulting from an increase in operating frequency is planned. A vibrating flow pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These functional studies could be combined usefully with further studies of differentiation by electron microscopy to determine the maturity of the air-blood barrier. Last, the use of exteriorized fetal catheters is not applicable to humans and significant technologic development is required to create a system comprising a detachable balloon (78) and a miniaturized remotely activated implantable pump (79), which could be used in human gestations.…”
Section: Discussionmentioning
confidence: 99%
“…These functional studies could be combined usefully with further studies of differentiation by electron microscopy to determine the maturity of the air-blood barrier. Last, the use of exteriorized fetal catheters is not applicable to humans and significant technologic development is required to create a system comprising a detachable balloon (78) and a miniaturized remotely activated implantable pump (79), which could be used in human gestations.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. (17), for example, have designed a preliminary‐stage implantable artificial heart with modular architecture. Each of the modules—such as a mechanical assistance device pumping unit, a sensory system that detects information in the body, an automatic control system performing the drive control, a transcutaneous energy transmission system, and a secondary implantable battery—was designed to perform a particular and independent function from other modules.…”
Section: Problems Arising From the Integral Architecture Of Bioartifimentioning
confidence: 99%
“…We have recently shown that prenatal cyclical occlusion for a repeated regimen of 47 hour occlusion with 1 hour release performed between 110 and 138 days gestation induces optimal lung growth and differentiation in the ovine model of CDH (Figure 2). 168 At present the cellular mechanisms whereby increased fetal lung expansion leads to increased rates of lung tissue growth and differentiation are unknown. At present this system is however not applicable to humans as exteriorized fetal catheters were used.…”
Section: Cdh Lung Response To Tracheal Occlusionmentioning
confidence: 99%